PERAN MGMP DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU PAI SMP DI RAYON 01 KABUPATEN PANDEGLANG - Aat Jumiat; Muhajir Muhajir (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2019)
The objectives of this study are: 1) Knowing the implementation of the Islamic Religious Education (PAI) Subject Teacher Deliberation at SMP District 01, Pandeglang Regency 2) Knowing the pedagogical and professional competences of Islamic Religious Education (PAI) teachers of SMP in District 01 Pandeglang Regency 3) Knowing the role of MGMP in improving Pedagogic and professional competence for Islamic Education Middle School teachers in District 01, Pandeglang Regency. This research is a qualitative research with descriptive analysis method. Data collection techniques use source triangulation, namely techniques for obtaining data from different sources with the same techniques such as observation, observation, interviews, and documentation to obtain data about the role of MGMP in improving pedagogical competence and professional competence of Islamic religious education teachers in Rayon 01 pandeglang district. Activities in data analysis by reducing data, presenting data systematically and drawing conclusions. The results of the study revealed that the pedagogical and professional competences of Islamic religious education teachers in District 01 of Pandeglang Regency were categorized as good, this could be seen from the aspects of learning planning, aspects of learning implementation, aspects of learning evaluation, aspects of educational qualifications, aspects of teacher certification and aspects of pedagogical competence. professional teachers in general. The research also found that the role of the MGMP was very significant in increasing the pedagogical and professional competence of Islamic religious education teachers in District 01, Pandeglang Regency.